Wild pea (Pisum sativumPisum sativum L. subsp. elatius (Bieb.) Aschers. et Graebn. s.l.) at the periphery of its range: Zagros Mountains - O. E. Kosterin; V. S. Bogdanova; A. V. Mglinets (Вавиловский журнал генетики и селекции, 2020)
Characteristics of wild peas and their habitats at the periphery of the range are interesting with respect to their potential importance for pre-breeding programs aimed at selection for different environmental conditions. However, wild pea diversity in peripheral regions is insufficiently represented in the existing germplasm collections. In such regions, wild pea populations are rare, small in size and suffer from climatic change and land exploitation, hence their focused search is strongly desirable. A two-week-long expedition to Iran in May 2017 revealed two small populations of the wild pea (Pisum sativum subsp. elatius) in the Zagros Mts, in Aligudarz and Khorramabad Districts of Lorestan Province, Iran, at elevations of 1841 and 1971 m a.s.l., respectively. Their habitats are briefly described. Two pea accessions derived from them, CE9 and CE10, were characterised for some visible and molecular characters. These peas appeared to belong to the evolutionary lineage B, recognised by us earlier in P sativum as opposed to the so-called lineage AC. They contain a unique non-conservative substitution in subtype 5 of histone H1 and turned to be most related to some wild pea accessions originating from southern and south-eastern Turkey and Golan Heights. Scarce information available on wild pea occurrence in Iran suggests their existence in the south-western principal slope of Zagros Mts and southern principal slopes of Elborz and Kopet Dagh Mts. It was found that wild peas representing the evolutionary lineage B produce poorly open and poorly coloured flowers (as reported by us earlier) only in the greenhouse conditions but normally pigmented and open flowers in the wild and mesh houses at open air in Israel. Some issues of pea taxonomy are discussed.